New Late Miocene Dromomerycine Artiodactyl from the Amazon Basin: Implications for Interchange Dynamics. (May 2014) - Prothero, Donald R.; Campbell, Kenneth E.; Beatty, Brian L.; Frailey, Carl D.
Abstract : A new dromomerycine palaeomerycid artiodactyl, Surameryx acrensis new genus new species, from upper Miocene deposits of the Amazon Basin documents the first and only known occurrence of this Northern Hemisphere group in South America. Osteological characters place the new taxon among the earliest known dromomerycine artiodactyls, most similar to Barbouromeryx trigonocorneus, which lived in North America during the early to middle Miocene, 20–16 Ma. Although it has long been assumed that the Great American Biotic Interchange (GABI) began with the closure of the Isthmus of Panama in the late Pliocene, or ca. 3.0–2.5 Ma, the presence of this North American immigrant in Amazonia is further evidence that terrestrial connections between North America and South America through Panama existed as early as the early late Miocene, or ca. 9.5 Ma. This early interchange date was previously indicated by approximately coeval specimens of proboscideans, peccaries, and tapirs in South America and ground sloths in North America. Although palaeomerycids apparently never flourished in South America, proboscideans thrived there until the end of the Pleistocene, and peccaries and tapirs diversified and still live there today.